Die Komparativ- und Superlativformen besser/am besten/das Beste als Varianten in modalen Vergleichskonstruktionen: Eine Pilotstudie zu Sprach- und Ausdrucksvarianten im Deutschen und Italienischen - Höhmann, Doris (Linguistik Online, 2021)
It is well known that linguistic variants play a key role in the acquisition of language skills in the first, second or foreign language as well as in writing and translation processes and in general in communicative interactions. Thus, a major research goal is the systematic investigation of intra- and interlinguistic variation. Due to its complexity, its qualitative-quantitative analysis continues to be a challenging issue, but it seems to become more and more feasible thanks to both the possibility of compiling very large corpora and the availability of high-performing corpus-linguistic tools.The paper discusses a corpus-linguistic pilot study concerning the use of besser, am besten and das Beste as pragmatic markers in a cross-linguistic perspective. In particular, the analysis focusses on selected superlative and comparative constructions on the left periphery used for expressing advice. The data basis consists mainly of German and Italian comparable very large web corpora and, to a lesser extent, of bilingual sentence pairs drawn from parallel corpora. As will be shown, even restricting the analysis to a very small segment of microvariation, in both languages the modal constructions appear to be characterized by the combination of numerous overlapping and interplaying variants and by different tendencies in language use.